Pains of Reentry Revisited - Durnescu, Ioan (International journal of offender therapy and comparative criminology, 2019)
Based on an ethnographic study with 58 participants released from a Romanian prison, this study revisits the pains of release and illustrates the complexity of the reentry process. Some of the pains of reentry seem universal while others seem to be context dependent. In the same time, some pains of release are personal, others social, while others are structural. Concepts of intersectionality and the multi-level model of reentry are discussed, and further suggestions for research are advanced.